Modelo de avaliação de impacto ambiental utilizando a teoria dos conjuntos fuzzy: um estudo de caso para a indústria automobilística - França, Lucirene Vitória Góes [UNESP] (2015)
The process of Environmental Impact Assessment (EIA) emerged in the 1960s, in US and began to be used in Brazil, from the 1970s, mainly for environmental licensing. It consists of a set of procedures used to predict, recover and / or mitigate the damage caused to the environment. Studies for the optimization of this process are often made in order to seek tools that help in decision making and speeding up the release of environmental licenses. The main methods used for prediction and assessment of impacts are: checklists, interaction matrices, interaction networks, overlay maps and simulation models. This work presents a methodology that applies the Fuzzy Set Theory to be used in the EIA process. The intention is to show a tool to assist in the environmental impact assessment and / or allows it to be carried out more widely. From the parameters: duration, temporality, reversibility and Magnitude, presented in the impact assessment matrix of the Environmental Impact Statement (EIS) of an automobile enterprise, was built two rules-based systems to determine the significance and relevance of impacts. The results were very significant so that the use of the methodology demonstrated much interesting to make integrated analysis of the parameters, which usually not occur in EIAs because these make analysis a fragmented way without explaining the form of aggregation of variables